2020
DOI: 10.1029/2019jf005436
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dust Deposition Varies by Season and Elevation in the Colorado Front Range, USA

Abstract: As atmospheric dust deposition continues to increase across the southwestern United States, it has the potential to alter ecosystem productivity and structure by delivering nutrients, base cations, and pollutants to remote mountain sites. Due to the sparse distribution of dust monitoring sites, open questions remain about the spatial and temporal variability of dust fluxes and composition across mountainous terrain. We present a 1 year (November 2017 to November 2018) record of seasonal dust fluxes and composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
2
16
0
Order By: Relevance
“…However, it is unlikely that precipitation chemistry on Niwot Ridge is derived exclusively from Colorado sources. For example, Heindel et al (2020) found seasonal patterns in dust deposition that were driven by wind patterns that incorporated local and regional source areas similar to those described by Baron and Denning (1993). From a study in Rocky Mountain National Park, Gebhardt et al (2011) estimated that only 30% to 45% of sulfur dioxide and N‐containing species on the eastern side of the Continental Divide were from sources within Colorado, with the rest coming from other states and international sources.…”
Section: Discussionmentioning
confidence: 70%
“…However, it is unlikely that precipitation chemistry on Niwot Ridge is derived exclusively from Colorado sources. For example, Heindel et al (2020) found seasonal patterns in dust deposition that were driven by wind patterns that incorporated local and regional source areas similar to those described by Baron and Denning (1993). From a study in Rocky Mountain National Park, Gebhardt et al (2011) estimated that only 30% to 45% of sulfur dioxide and N‐containing species on the eastern side of the Continental Divide were from sources within Colorado, with the rest coming from other states and international sources.…”
Section: Discussionmentioning
confidence: 70%
“…Although prevailing winds are westerly, thermally‐driven easterlies transport air masses from the Boulder‐Denver metro area and the eastern agricultural plains up into the mountains on regular diurnal cycles during the spring and summer months (Blanken et al., 2009; Heindel et al., 2020; Losleben et al., 2000). These seasonal easterlies have previously been connected to increased spring and summer Nr loads, ammonia concentrations, dust deposition, and ozone concentrations (Gebhart et al., 2011; Heindel et al., 2020; Sullivan et al., 2016). Synoptic‐scale upslope events also occur during the fall months and have the potential to transport N pollution to higher elevations (Benedict, Day, et al., 2013), but we found much lower concentrations and loads across the elevation transect during the fall.…”
Section: Discussionmentioning
confidence: 99%
“…The vast sedimentary carbonate formations around the Lake Urmia basin and marl formations to the east (Figure S5) support the reason why Ca 2+ EF and NSSF values are elevated. Although outside the scope of this work, there can be influence from elevation gradients and land use on crustal emissions . Our results confirm that crustal aerosol particles are significant in the region as agents in rainwater, which has implications for cloud microphysical processes and for neutralization of acidic components.…”
Section: Discussionmentioning
confidence: 99%
“…Although outside the scope of this work, there can be influence from elevation gradients and land use on crustal emissions. 103 Our results confirm that crustal aerosol particles are significant in the region as agents in rainwater, which has implications for cloud microphysical processes and for neutralization of acidic components. This is important for other study regions too to indicate that wind-blown salt and crustal matter not only impact aerosol properties but also clouds and rain.…”
mentioning
confidence: 99%